Recent Advances and Future Perspectives of Single‐Photon Avalanche Diodes for Quantum Photonics Applications. Issue 2 (22nd December 2020) - Ceccarelli, Francesco; Acconcia, Giulia; Gulinatti, Angelo; Ghioni, Massimo; Rech, Ivan; Osellame, Roberto
Abstract: Photonic quantum technologies promise a revolution of the world of information processing, from simulation and computing to communication and sensing, thanks to the many advantages of exploiting single photons as quantum information carriers. In this scenario, single‐photon detectors play a key role. On the one hand, superconducting nanowire single‐photon detectors (SNSPDs) are able to provide remarkable performance on a broad spectral range, but their applicability is often limited by the need of cryogenic operating temperatures. On the other hand, single‐photon avalanche diodes (SPADs) overcome the intrinsic limitations of SNSPDs by providing a valid alternative at room temperature or slightly below. In this paper, the authors review the fundamental principles of the SPAD operation and provide a thorough discussion of the recent progress made in this field, comparing the performance of these devices with the requirements of the quantum photonics applications. In the end, the authors conclude with their vision of the future by summarizing prospects and unbeaten paths that can open new perspectives in the field of photonic quantum information processing. Abstract : Photonic quantum technologies promise a revolution of the world of information processing thanks to the many advantages of exploiting single photons as quantum information carriers. In this scenario, single‐photon avalanche diodes play a key role. In this paper, the authors provide a thorough discussion of the recent progress made on these detectors, concluding with their vision of the future.